Zirconium nanoparticles based ligandless dispersive solid phase extraction for the determination of antimony in bergamot and mint tea samples by slotted quartz tube-flame atomic absorption spectrophotometry - Karlidag, Nazime Ebrar; Toprak, Munevver; Tekin, Zeynep; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
A sensitive and effective analytical method was developed to preconcentrate antimony from the bergamot and mint tea samples for its determination at trace levels by slotted quartz tube-flame atomic absorption spectrophotometry (SQT-FAAS) system. The developed method was based on vortex assisted ligandless dispersive solid phase extraction (VA-LDSPE) using zirconium nanoparticles (Zr-NPs) as sorbent material for the adsorption of the target analyte. All variables involved in the DSPE method (pH value, nanoparticle amount, mixing and eluent type/volume) were optimized to boost the absorbance signal of antimony. Using the optimal parameters, the method provided satisfactory detection and quantification limits of 8.0 and 26.8 mu g L-1, respectively. A 180 folds enrichment factor was achieved by the developed method when compared with the detection power of the FAAS. Linear range of the proposed method was found to be 30-250 mu g L-1, with a coefficient of determination value of 0.9992. The established Zr-NPs-VA-LDSPE-SQT-FAAS method was successfully implemented to bergamot tea samples in order to check accuracy and applicability. The obtained recovery values ranged between 93-102%, and this demonstrated that the complex matrices tested did not affect the accuracy of quantifying antimony.
Keywords: Antimony; Zirconium nanoparticles; Flame atomic absorption spectrophotometry; Slotted quartz tube; Ligandless dispersive solid phase extraction; Bergamot and mint tea; Food analysis; Food composition; SPECIATION ANALYSIS; DROP MICROEXTRACTION; PRECONCENTRATION; LEAD; SPECTROMETRY; MAGNETITE; POLYMER; WATER; FOOD; Chemistry; Food Science & Technology